2020
DOI: 10.1038/s41408-019-0272-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq profiling of deregulated miRs in CLL and their impact on clinical outcome

Abstract: Abnormal expression patterns of regulatory small non-coding RNA (sncRNA) molecules such as microRNAs (miRs), piwi-interacting RNAs (piRNAs), and small nucleolar RNAs (snoRNAs) play an important role in the development and progression of cancer. Identification of clinically relevant sncRNA signatures could, therefore, be of tremendous translational value. In the present study, genome-wide small RNA sequencing identified a unique pattern of differential regulation of eight miRs in Chronic Lymphocytic Leukemia (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
2
25
0
5
Order By: Relevance
“…It is now possible to use next-generation sequencing (NGS) as an extensive study to search for miRNA molecules that can serve as prognostic and predictive factors in CLL. Kaur et al ( 50 ) conducted a genome-wide small RNA sequencing study to reveal a unique pattern of differential regulation of eight miRNAs in CLL. Upregulated miRNAs include miR-1295a, miR-155 and miR-4524a; while miR-30a, miR-423, miR-486*, let-7e and miR-744 are downregulated ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now possible to use next-generation sequencing (NGS) as an extensive study to search for miRNA molecules that can serve as prognostic and predictive factors in CLL. Kaur et al ( 50 ) conducted a genome-wide small RNA sequencing study to reveal a unique pattern of differential regulation of eight miRNAs in CLL. Upregulated miRNAs include miR-1295a, miR-155 and miR-4524a; while miR-30a, miR-423, miR-486*, let-7e and miR-744 are downregulated ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kaur et al ( 50 ) conducted a genome-wide small RNA sequencing study to reveal a unique pattern of differential regulation of eight miRNAs in CLL. Upregulated miRNAs include miR-1295a, miR-155 and miR-4524a; while miR-30a, miR-423, miR-486*, let-7e and miR-744 are downregulated ( 50 ). This demonstrated that miR-4524a and miR-744 are significantly associated with CLL risk and time to first treatment ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, it has been observed that miR-744 was a promising tumor molecular marker in some tumor tissues or serum (Table 1), including chronic lymphocytic leukemia [8], hepatocellular carcinoma [12], osarcoteosma [18] and gastric cancer [31]. However, there is still no study on the expression of miR-744 in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The role of both intracellular and extracellular (i.e. cell free and packaged in extracellular vesicles) miRNAs in CLL have revealed at least 10-20 miRNAs associated with varying disease characteristics [51][52][53][54][55][56][57]. Exosomes are the smallest known extracellular vesicles (50-100 nm) with distinct biochemical properties that carry cellular components, such as proteins, peptides, lipids, mRNA, and miRNAs [58].…”
Section: Potential Circulating Factors Associated With Tumor Cell Growth In Vitromentioning
confidence: 99%